STUDY ON THE FISHERY AND BIOLOGY OF THE MANTIS SHRIMP ORATOSQUILLA NEPA (LATREILLE) OF SOUTH KANARA COAST DURING 1979-83 - Sukumaran, K K (Indian Journal of Fisheries, 2011)
The catches of Oratosquilla nepa along the South Kanara coast were maximum during 1981-82, amounting to 2543.3 t at a catch rate of 16.5 kg|h at Mangalore and to 1868.8 t at 16.7 kg|h at Malpe. The catch was high during January- April. A mean growth of 7-8 mm|month was indicated. The species appear to grow to it length of about 108 mm by the end of first year and to live for 15-16 months. In the development of the ovary, five maturity stages, ie., immature, early maturing, late maturing, mature and spent|spent-recovering, have been recognised. The size at maturity at 50% level is estimated at 95 mm. The spawning season is found to be extending from December to October with peaks during March-June and September-October. Females generally outnumbered males. Chi-square test showed significant variation from 1:1 ratio in the distribution of sexes. The fecundity is estimated at 6,78,200 in a female measuring 108 mm body length. The growth parameters, 1 a, and c.k were estimated at 143 mm and 0.2877 respectively. The mean.monthly Z values were 0.9767 for males and 0.923d for females